Organizational-Pedagogical Conditions of Training Future Naval Infantry Units Officers by Means of Information-Communication Technologies - Zaitsev, Ihor (Pedagogical Discourse, 2020)
Transformation processes in Ukraine need to increase the efficiency of training future specialists in the system of higher education, in particular in higher military educational institutions. At the present stage, the system of military education must ensure the effective training of future naval infantry units officers for military professional activities in accordance with modern requirements and state standards of education. Modernization of Ukraine’s system of higher military education in the context of the Bologna Declaration, integration of Ukraine’s system of education into the European and world educational community, setting up cooperation of Ukrainian higher military educational institutions with foreign partners from NATO member states, and objective need of training of highly qualified military specialists stipulate the need of search for new, effective forms, methods, means, ways of organizing the educational process, reforming the content of military education. Currently, the processes of modernization of the national system of higher military education are underway in accordance with the Bologna Declaration. In view of this, an important area of researches has naturally become information-communication technologies of the organization of the educational process, in particular those used in the training of future naval infantry units officers. Therefore, the article analyzes the basic organizational-pedagogical conditions of the training of future naval infantry units officers by means of information-communication technologies. It is established and substantiated that the training of future naval infantry units officers for professional activities with the use of information-communication technologies will be more effective under the following organizational-pedagogical conditions: organization of independent work of cadets with the use of ICT tools; introduction of modern computer-based methods and tools of organizing the educational process in higher military educational institutions; use of the project method in the training of future officers.